Evaluation of the Role of Service Quality Aspects in Enhancing Customer Loyalty of Indibiz Products at PT. Telkom Indonesia Witel Yogyakarta - Firmansyah, Aldy Arya; Fadhilla, Hanifa Nur (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to evaluate the role of service quality in enhancing the customer loyalty of the IndiBiz product provided by PT. Telkom Indonesia Witel Yogyakarta. Customer loyalty is crucial for maintaining market share in the competitive telecommunications industry. The Stimulus-Organism-Response (S-O-R) theory is utilized to analyze the relationship between service quality (stimulus) and customer loyalty (response). Service quality is analyzed through five dimensions: Tangibles, Reliability, Responsiveness, Empathy, and Assurance. This research employs a qualitative approach, conducting observations and in-depth interviews with five IndiBiz customers in Yogyakarta. The findings indicate that Reliability and Responsiveness play a significant role in shaping customer loyalty. Network reliability and prompt responses from customer service are the primary factors driving loyalty. Furthermore, staff empathy also strengthens the emotional connection with customers. However, issues with the MyIndiBiz application act as a barrier to optimally enhancing loyalty. Overall, while high service quality can strengthen customer loyalty, the company needs to improve sub-optimal aspects to retain it. Future research is recommended to explore the impact of improvements to the MyIndiBiz application on loyalty, increase the number of respondents, and analyze other factors such as price and brand image for a more comprehensive understanding.